Subgingival biodiversity in subjects with uncontrolled type‐2 diabetes and chronic periodontitis. (4th July 2012) - Casarin, R. C. V.; Barbagallo, A.; Meulman, T.; Santos, V. R.; Sallum, E. A.; Nociti, F. H.; Duarte, P. M.; Casati, M. Z.; Gonçalves, R. B.
<x xml:space="preserve">Abstract</x> Background and Objective: There is a bidirectional relationship between periodontal disease and type‐2 diabetes mellitus (DM). Inflammatory mediators may negatively affect glycemic control, and increased glucose levels and resultant glycation end‐products may alter the host response against bacterial infection. However, no agreement has been reached regarding the effect of DM on periodontal subgingival microbiota. Therefore, the purpose of the present study was to compare the subgingival biodiversity in deep periodontal pockets of subjects with chronic periodontitis and either uncontrolled type‐2 diabetes or no diabetes using 16S rRNA gene cloning and sequencing. Material and methods: Twelve subjects with uncontrolled type‐2 diabetes (glycated hemoglobin > 8%) and eleven nondiabetic subjects presenting severe and generalized chronic periodontitis were selected. Subgingival biofilm from periodontal pockets > 5 mm were assessed using the 16S rRNA gene cloning and sequencing technique. Results: Significant differences were observed in subgingival microbiota between diabetic and nondiabetic subjects. Diabetic subjects presented higher percentages of total clones of TM7, Aggregatibacter, Neisseria, Gemella, Eikenella, Selenomonas, Actinomyces, Capnocytophaga, Fusobacterium, Veillonella and Streptococcus genera, and lower percentages of Porphyromonas, Filifactor, Eubacterium, Synergistetes, Tannerella and Treponema genera than nondiabetic individuals (p < 0.05). Moreover, some phylotypes, such as Fusobacterium nucleatum, Veillonella parvula, V. dispar and Eikenella corrodens were detected significantly more often in diabetic subjects than in nondiabetic subjects (p < 0.05). Conclusion: Subjects with uncontrolled type‐2 diabetes and chronic periodontitis presented significant dissimilarities in subgingival biodiversity compared with nondiabetic subjects.